Shedding light on the relative DNA contribution of two persons handling the same object. (September 2016) - Oldoni, F.; Castella, V.; Hall, D.
Highlights: Progressive increase of the second user's DNA contribution, relative to the first user, was observed over time in 218 out of 234 (93%) simulated traces. Single-source DNA profile was shown to represent only 3 out of 234 (1%) traces simulated on objects touched by two users. Partial/full DNA profiles of known participants were indirectly transferred in 9 cases (4%). Apart from 1 case out of 234, indirectly transferred DNA represented the minor fraction of the mixed DNA profiles observed. Abstract: Traces collected on crime scene objects frequently result in challenging DNA mixtures from several contributors in different DNA proportions. Understanding how the relative proportion of DNA deposited by different persons who handled the same object evolves through time has important bearings. For instance, this information may help determine whether the major contributor in a mixed DNA profile is more likely to correspond to the object owner or to the person who may have stolen this object. In this perspective, a simulation-based protocol was designed where randomly paired participants were asked to act either as first (object owner) or second (last) users. The first user was asked to handle/wear 9 different plastic-, metal-, nitrile- and fabric-made objects, commonly found at burglary/robbery crime scenes, for a minimum of 20 min during 8 or 10 consecutive days. The second user subsequently used them for 5, 30 or 120 min in three distinct simulation sessions. The analysis of the relative DNA contribution on the resulting 234 mock DNA traces revealed a large variability in the contribution depending on the time, substrate and pairs of participants. Despite this, a progressive increase of the second user's DNA contribution, relative to the first user, was observed over time in 93% of the traces. The second user was shown to become the major contributor in approximately 15%, 33% and 55% of the traces recovered from objects used for 5, 30 and 120 min, respectively. Single-source DNA profiles were shown to represent only 1% of the traces. In addition, the DNA profiles of 165 out of 234 (71%) simulated traces displayed extra alleles. Most of these occurred in the minor fraction of mixed DNA profiles and were interpreted as artefacts. Nevertheless, DNA profiles of known participants either involved or not in the simulations were observed in 9 cases (4%). This confirms that indirect DNA transfer should be taken into account when interpreting "touch" DNA evidence.